2009
DOI: 10.1007/s11595-009-5694-0
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and thermoelectric properties of SiO2/β-Zn4Sb3 nanocomposite materials

Abstract: A series of SiO 2 /β-Zn 4 Sb 3 core-shell composite particles with 3, 6, 9, and 12 nm of SiO 2 shell in thickness were prepared by coatingβ-Zn 4 Sb 3 microparticles with SiO 2 nanoparticles formed by hydrolyzing the tetraethoxysilane in alcohol-alkali-water solution. SiO 2 /β-Zn 4 Sb 3 nanocomposite thermoelectric materials were fabricated with these core-shell composite particles by spark plasma sintering (SPS) method. Microstructure, phase composition, and thermoelectric properties of SiO 2 /β-Zn 4 Sb 3 nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In terms of doping Al element, the Seebeck coefficient shows a similar trend as that of doping Cu. The thermal conductivity is also lower than that of Zn 4 Sb 3 as expected by Cui et al Ruan et al [35] reported that for Zn 4 Sb 3 coated with a layer of SiO 2 film, the results showed that the coating does not induce phase transformation, but SiO 2 film can effectively reduce thermal conductivity and increase the ZT value. …”
Section: Vacuum Sintering and Vacuum Hot Pressing Of Bulk Zn 4 Sb 3 Amentioning
confidence: 55%
“…In terms of doping Al element, the Seebeck coefficient shows a similar trend as that of doping Cu. The thermal conductivity is also lower than that of Zn 4 Sb 3 as expected by Cui et al Ruan et al [35] reported that for Zn 4 Sb 3 coated with a layer of SiO 2 film, the results showed that the coating does not induce phase transformation, but SiO 2 film can effectively reduce thermal conductivity and increase the ZT value. …”
Section: Vacuum Sintering and Vacuum Hot Pressing Of Bulk Zn 4 Sb 3 Amentioning
confidence: 55%
“…Influence of Redispersible Polymer Powder on Thermal-insulation Mortar Properties. The main purpose of mixing with redispersible polymer powder is to improve the workability and bonding strength of mortar [2][3]. It can be seen from Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that Ba y Co 4 Sb 12 nanocomposites with dispersed fullerene or barium fulleride have been successfully fabricated by the SPS and solid state reaction (Shi et al, 2007). Also, SiO 2 /β-Zn 4 Sb 3 core-shell nanocomposite particles with the low thermal conductivity were synthesized by SPS method (Ruan & Xiao, 2007). Moreover, CoSb 3-x Te x skutterudite polycrystals were synthesized by SPS along with mechanical alloying (Liu et al, 2007).…”
Section: Spark Plasma Sinteringmentioning
confidence: 99%
“…β phase Zn 4 Sb 3 is a structurally disordered intermetallic compound at moderate temperature range 450 K-650 K. So β phase Zn 4 Sb 3 is a promisng nanocomposite material which possesses potential low thermal conductivity. (Ruan & Xiao, 2007).…”
Section: Zn 4 Sbmentioning
confidence: 99%